Two Novel Myelin Protein Zero Mutations in a Group of Chinese Patients - Chen, Bin; Zhang, Zaiqiang; Chen, Na; Li, Wei; Pan, Hua; Wang, Xingao; Ren, Yuting; Shi, Yuzhi; Tai, Hongfei; Niu, Songtao (Frontiers in Neurology, 2021)
Mutations in the myelin protein zero (MPZ) gene are responsible for the autosomal dominant Charcot-Marie-Tooth disease (CMT). We summarized the genetic and clinical features of six unrelated Chinese families and the genetic spectrum of Chinese patients with MPZ mutations. Our study reports data from a group of Chinese patients consisting of five males and one female with the age of disease onset ranging from 16 to 55 years. The initial symptom in all the patients was weakness of lower limbs. Electrophysiological presentations suggested chronic progressive sensorimotor demyelinating polyneuropathy. Overall six mutations were identified in the cohort, including four known mutations [c.103G＞T (p.D35Y), c.233C>T (p.S78L), c.293G>A (p.R98H) and c.449-1G>T], and two novel mutations [c.67+4A>G with a mild CMT1B phenotype, and (c.79delG) p.A27fs with a rapidly progressive CMT1B phenotype]. According to the literature review, there are 35 Chinese families with 28 different MPZ mutations. The MPZ mutational spectrum in Chinese patients is very heterogeneous and differs from that of Japanese and Koreans individuals, although they do share several common hot spot mutations.